Association of short-term exposure to PM2.5 and PM10 with hospitaliza-tion risk and excess expenses burden of unstable angina pectoris patients in Yichang city - Chuangang FAN; Zhongcheng YANG; Zaoxia WANG; Jing WANG; Xiuqing CUI; Xiang LI; Xi LUO; Xiaoyan MING; Shuguang XIE (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the association of short-term exposure to particulate matter ≤ 2.5 and ≤ 10 μm in aerodynamic diameter (PM2.5 and PM10) with hospitalization risk and excess expenses burden of unstable angina pectoris (UAP) patients for providing a reference to UAP prevention. MethodsMedical records of 11 334 UAP patients hospitalized from 2019 through 2021 were collected from 6 hospitals in Yichang city, Hubei province. Local data over the same period on daily ambient air pollutants and meteorological factors were also collected from five national automatic monitoring stations and municipal weather bureau. Time-stratified case-crossover design and conditional logistic regression model were adopted to analyze the association of each 10 μg/m3 change in ambient air PM2.5 and PM10 concentration with UAP hospitalization risk and excess economic burden. ResultsIn total, 11 334 UAP case days were matched to 38 540 control days. In single pollutant model analysis, a 10 μg/m3 increase in PM2.5 and PM10 was associated with the increased UAP hospitalization risk of 0.92% and 0.89% on lag day 0 (Lag0), 0.73% and 0.62% on Lag1, 1.00% and 0.92% over lag days 0 - 1 (Lag0 - 1), and 0.84% and 0.85% over Lag0 - 2, respectively. After adjusting for sulfur dioxide, nitrogen dioxide, carbon monoxide, ozone, temperature and relative humidity in multi-pollutant model analysis, PM2.5 was significantly associated with increased UAP hospitalization risk on days from Lag0 to Lag4 and over days from Lag0 - 1 to Lag0 - 5 and the highest increased risk was observed over Lag0 - 2 (excess risk [ER] = 1.86%, 95% confidence interval [95%CI]: 0.46% - 3.27%); PM10 showed a significant impact on UAP hospitalization risk on Lag0, Lag1, and over Lag0 - 1 and Lag0 - 2, and with the highest increased risk over Lag0 - 1 (ER = 1.19%, 95%CI: 0.23% - 2.16%). Further stratified analysis indicated that the significant association still existed for gender and seasonal subgroup patients. For males, PM2.5 and PM10 was associated with the highest increased risk over Lag0 - 1 (ER = 2.69%, 95%CI: 0.40% - 5.03%) and on Lag0 (ER = 1.59%, 95%CI: 0.47% - 2.72%). In warm season, PM2.5 and PM10 was associated with the highest increased risk over Lag0 - 2 (for PM2.5: ER = 2.69%, 95%CI: 0.40% - 5.03%; for PM10: ER = 1.59%, 95%CI: 0.47% - 2.72%). During 2019 - 2021 in Yichang city, the increments of ambient air PM2.5 and PM10 were associated with the increased UAP hospitalizations of 109 and 28 and excessive UAP-related economic burden of 1.554 and 0.373 million Chinese Yuan based on China's current secondary air quality control standards, respectively. Conclusion Short-term exposure to increased ambient air PM2.5 and PM10 can significantly increase hospitalization risk and excess expenditure of unstable angina pectoris patients in Yichang city.